2014
DOI: 10.1210/en.2013-2081
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mouse In Vitro Fertilization Model to Understand the Developmental Origins of Health and Disease Hypothesis

Abstract: The Developmental Origins of Health and Disease hypothesis holds that alterations to homeostasis during critical periods of development can predispose individuals to adult-onset chronic diseases such as diabetes and metabolic syndrome. It remains controversial whether preimplantation embryo manipulation, clinically used to treat patients with infertility, disturbs homeostasis and affects long-term growth and metabolism. To address this controversy, we have assessed the effects of in vitro fertilization (IVF) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
3
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 60 publications
11
161
3
3
Order By: Relevance
“…There are several reports pointing out that IVF may relate with abnormal emotional behaviors in adult mouse offspring [60–64]. In this study, Sey/+ mice born from IVF showed decreased USV vocalizations and less anxiety, which is similar to rSey 2 /+ rats born from natural mating [37].…”
Section: Discussionsupporting
confidence: 61%
“…There are several reports pointing out that IVF may relate with abnormal emotional behaviors in adult mouse offspring [60–64]. In this study, Sey/+ mice born from IVF showed decreased USV vocalizations and less anxiety, which is similar to rSey 2 /+ rats born from natural mating [37].…”
Section: Discussionsupporting
confidence: 61%
“…In some studies, only female mice exhibited metabolic effects in response to ART procedures [66,67]. IVF and ICSI female offspring displayed impaired glucose tolerance compared to naturally conceived controls, while no effects were detected in IVF or ICSI males [66].…”
Section: Evidence That Art Can Increase the Risk Of Cardiometabolimentioning
confidence: 99%
“…During embryonic development, organisms exhibit a high level of developmental plasticity allowing for alterations of the genetic landscape in response to the surrounding environment which can ultimately result in a broad range of adult phenotypes (Feuer et al 2014). It is within these genetic and epigenetic alterations that an increased risk of developing diseases in adulthood occurs.…”
Section: Introductionmentioning
confidence: 99%